2014
DOI: 10.1016/s1995-7645(14)60281-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted extraction of phenolic compounds from Cratoxylum formosum ssp. formosum leaves using central composite design and evaluation of its protective ability against H2O2-induced cell death

Abstract: These results indicate the suitability of ultrasound-assisted extraction for the extraction of phenolic compounds from Cratoxylum formosum ssp. formosum leaves. This phenolic-enriched extract can be used as valuable antioxidant source for health benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 16 publications
4
29
0
Order By: Relevance
“…In the case of the extraction with microwaves, the energy is absorbed efficiently by compounds contained in the plant material, therefore, the inner temperature dramatically increases and facilitates mass transfer of secondary metabolites in the solvent, allowing a fast and efficient extraction (ZHANG et al, 2011). A similar effect to this work was found by Yingngam et al (2014) who reported a more efficient extraction of polyphenols from Cratoxylum formosum ssp. Formosum leaves by ultrasound than conventional method by heating.…”
supporting
confidence: 77%
“…In the case of the extraction with microwaves, the energy is absorbed efficiently by compounds contained in the plant material, therefore, the inner temperature dramatically increases and facilitates mass transfer of secondary metabolites in the solvent, allowing a fast and efficient extraction (ZHANG et al, 2011). A similar effect to this work was found by Yingngam et al (2014) who reported a more efficient extraction of polyphenols from Cratoxylum formosum ssp. Formosum leaves by ultrasound than conventional method by heating.…”
supporting
confidence: 77%
“…The recent study confirms that ultrasound-assisted extraction is an effective, easy in operation, inexpensives and reliable, method for extraction of polyphenols from plant material (Carrera et al, 2012;González-Centeno et al, 2015;Khan et al, 2010;Muñiz-Márquez et al, 2013;Melecchi et al, 2006;Wang et al, 2013;Yingngam et al, 2014).…”
Section: Resultssupporting
confidence: 61%
“…Up to now, several extraction techniques have been reported for extracting phenolic compounds from herbal medicine, include: maceration (Diouf et al, 2009), solvent extraction (Anagnostopoulou et al, 2006;Jeong et al, 2004;Li et al, 2006;Xu et al, 2007), Soxhlet extraction and heat reflux extraction (Jun et al, 2011;Oniszczuk et al, 2013;Waksmundzka-Hajnos et al, 2007,2008, ultrasound-assisted extraction (Carrera et al, 2012;Diouf et al, 2009;González-Centeno et al, 2015;Khan et al, 2010;Roseiro et al, 2013;Yingngam et al, 2014), microwave-assisted extraction (Dahmoune et al, 2014(Dahmoune et al, ,2015Spigno et al, 2007), accelerated solvent extraction (Luthria, 2008;Oniszczuk et al, 2014;Waksmundzka-Hajnos et al, 2008) and supercritical fluid extraction (Giannuzzo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Cratoxylum formosum subsp. pruniflorum (Kurz) Gogelein, commonly known in Thai as 'tio-khon' is a tree of the family Hypericaceae and is widely distributed in dry deciduous dipterocarp forest in many southeast Asian countries (Boonnak et al, 2006) and China (Yingngam et al, 2014). In Thailand, there are six species of this genus (Smitinand, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous phytochemical studies on C. formosum subsp. pruniflorum reported antioxidant activity of the ethanolic leaf extract (Yingngam et al, 2014), anti-inflammatory activity of phenolic compounds, xanthones, quinone, quercetin and its glycosides from leaves (Choi et al, 2012;Xiong et al, 2014), anticancer activity of ethanolic twig extract, hot water leaf extract and ethanolic leaf extract (Machana et al, 2012;Issara-Amphorn and T-Thienprasert, 2014) antibacterial and cytotoxic activities of xanthones, anthraquinones and qiunonoids from the roots and bark (Boonnak et al, 2006;Boonsri et al, 2006;Boonnak et al, 2007), antifungal and cytotoxic activity of gum extract (Thaweboon et al, 2014), anti-gastric ulceration of ethanolic leaf extract in rats (Sripanidkulchai et al, 2010) and anti-proliferation and antimigration activity of human breast cancer MCF-7 cells from leaf extract (Buranrat et al, 2017).…”
Section: Introductionmentioning
confidence: 99%